High-Isolation wideband MIMO antenna with offset T-Shaped slots for 5G/WLAN applications - Chen, Shuyi; Lu, Na; Sun, Jiaxing; Zhou, Changfei; Li, Changxian; Wu, Di (Frontiers in Physics, 2022)
A broadband multiple-input multiple-output (MIMO) antenna with high isolation operating in 3.14–5.42 GHz (2.28 GHz, 53.3%) is proposed for 5G smartphones. An offset T-shaped slot with dual functions is employed to improve the bandwidth of one antenna element and enhance the isolation. Then, the double L-shaped stubs are loaded to improve the impedance matching of the other antenna in the MIMO antenna. Finally, the 2 × 2 MIMO antenna is constructed by four T-shaped monopole antennas, two double L-shaped stubs, and two offset T-shaped slots. The proposed MIMO antenna is first simulated and then experimentally tested with a good agreement. High isolation of greater than 15 dB, high antenna efficiency of more than 54%, and low envelope correlation coefficient (ECC) of smaller than 0.08 are realized within 3.14–5.42 GHz. These good performances indicate that the proposed antenna can be applied for MIMO applications in smartphones.